Opuntia Ficus Indica Edible Parts: A Food and Nutritional Security Perspective. Issue 5 (4th July 2022) - Barba, Francisco J.; Garcia, Cyrielle; Fessard, Amandine; Munekata, Paulo E. S.; Lorenzo, Jose M.; Aboudia, Aouatif; Ouadia, Adbelouahab; Remize, Fabienne
ABSTRACT: Cactus Opuntia ficus indica is widely distributed in (semi-) arid regions. Fruit and cladodes are processed into many food products. Cladodes are used as vegetables, but their main use is flour, which can partly substitute wheat or corn flour in bread, cookies or cakes. Fruit are mainly transformed into snacks, juices or minimally-processed foods. Mucilage, coloring extracts and antimicrobial extracts are valuable by-products of cactus processing. Fruit and cladodes are characterized by a high antioxidant activity. They contain ferulic acid as the predominant phenolic acid, rutin and isorhamnetin derivatives as the main flavonoids, and betalain pigments, but also lutein and beta-carotene, as the most abundant colored compounds present in skin and pulp. Bakery products containing cladode flour are enriched in fiber, minerals and polyphenols. Processing, through drying, heat treatment or innovative technologies, aims to preserve fruit nutritional and sensory characteristics. In recent years, lactic acid fermentation of plant-based foods demonstrated many benefits. Fermentation modifies vitamin C level, carotenoid, phenolic compound content and antioxidant activity. Moreover, fermentation of cladode pulp showed promising functional feature on inflammatory response through modulation of cytokine secretion. This opens new perspectives for the development of products with health benefits.